La gouvernance des lotissements via les contestations : exemple de la commune de Sèmè-Podji au Bénin - Adéothy Adegbinni; Moïse Chabi; Benoît T. Danvidé; Charles-Omer Avalla (Territoire en Mouvement)
Subdivision operations are conceived as instruments capable of planning the use of space and improving the living conditions of the population. In the commune of Sèmè-Podji, the process of implementing allotment operations sometimes leads to disputes by certain actors in the locality.The objective of this research is to study the effects of disputes over subdivision operations on the improvement of the urban living environment. To achieve this, an analysis of the documents relating to all the subdivision operations carried out in the municipality was carried out. This analysis was supported by field surveys with a sample of 272 people.The results obtained show that contests over subdivision operations sometimes delay the establishment of socio-community infrastructures. But they force the various actors involved to make compromises and thus relax the application of the directives of the rigid and incomprehensible administrative land organization in order to put in place a new form of land governance accepted by the population.